Motor Imagery of Speech: The Involvement of Primary Motor Cortex in Manual and Articulatory Motor Imagery - Maegherman, Gwijde; Nuttall, Helen E.; Devlin, Joseph T.; Adank, Patti (Frontiers in Human Neuroscience, 2019)
Motor imagery refers to the phenomenon of imagining performing an action without action execution. Motor imagery and motor execution are assumed to share a similar underlying neural system that involves primary motor cortex (M1). Previous studies have focused on motor imagery of manual actions, but articulatory motor imagery has not been investigated. In this study, transcranial magnetic stimulation (TMS) was used to elicit motor-evoked potentials (MEPs) from the articulatory muscles (orbicularis oris) as well as from hand muscles (first dorsal interosseous). Twenty participants were asked to execute or imagine performing a simple squeezing task involving a pair of tweezers, which was comparable across both effectors. MEPs were elicited at six timepoints (50, 150, 250, 350, 450, 550ms post-stimulus) to track the time-course of M1 involvement in both lip and hand tasks. The results showed increased MEP amplitudes for action execution compared to rest for both effectors at time points 350, 450 and 550ms, but we found no evidence of increased cortical activation for motor imagery. The results indicate that motor imagery does not involve M1 for simple tasks for manual or articulatory muscles. The results have implications for models of mental imagery of simple articulatory gestures, in that no evidence is found for somatotopic activation of lip muscles in sub-phonemic contexts during motor imagery of such tasks, suggesting that motor simulation of relatively simple actions does not involve M1.